1998
DOI: 10.1590/s0074-02761998000500015
|View full text |Cite
|
Sign up to set email alerts
|

Systematics and Population Level Analysis of Anopheles darlingi

Abstract: A new phylogenetic analysis of the Nyssorhynchus subgenus (Danoff-Burg and Conn, unpub. data)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
5
0
2
Order By: Relevance
“…The COI region sequences exhibited sufficient nucleotide diversity to be able to determine the occurrence of one haplotype per broodstock and another for F. subtilis, with 8 divergent sites being detected among the five broodstocks and 70 between L. vannamei and F. subtilis. The substitution rate presented by the COI gene was somewhat higher, allowing the detection of genetic differences between different populations of the same species (Conn, 1998;Lee, 2000;Gusmão et al, 2000). Although the genetic distances for the five L. vannamei broodstocks were close to zero (0.2 to 1%) the values were similar to those published by Gusmão et al (2000) for some penaeid species investigated using COI gene sequencing.…”
Section: Discussionsupporting
confidence: 75%
“…The COI region sequences exhibited sufficient nucleotide diversity to be able to determine the occurrence of one haplotype per broodstock and another for F. subtilis, with 8 divergent sites being detected among the five broodstocks and 70 between L. vannamei and F. subtilis. The substitution rate presented by the COI gene was somewhat higher, allowing the detection of genetic differences between different populations of the same species (Conn, 1998;Lee, 2000;Gusmão et al, 2000). Although the genetic distances for the five L. vannamei broodstocks were close to zero (0.2 to 1%) the values were similar to those published by Gusmão et al (2000) for some penaeid species investigated using COI gene sequencing.…”
Section: Discussionsupporting
confidence: 75%
“…Numerous studies were conducted on the population biology and genetics of An. darlingi showing the great heterogeneity between populations from different countries for both important behavioral determinants [45] and genetic markers [46,47]. The biting behaviour is varying from uni-modal to tri-modal and biting peaks were found for almost each hour between 6:00 PM and 6:00 AM [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, several isozyme and DNA-based studies reported levels of genetic differentiation consistent with a monotypic species throughout the species' range [9-11]. Although mtDNA history revealed some genetic divergence between South and Central American populations [12-14], complete mtDNA genomes of A. darlingi did not provide support for speciation within the taxon [6]. Nuclear microsatellite markers revealed restricted contemporary gene flow among A. darlingi populations over broad geographical ranges (continental scale) but mainly due to isolation by distance [15-17].…”
Section: Introductionmentioning
confidence: 99%